If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -3) = 8 + 3x Reorder the terms: 2(-3 + x) = 8 + 3x (-3 * 2 + x * 2) = 8 + 3x (-6 + 2x) = 8 + 3x Solving -6 + 2x = 8 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -6 + 2x + -3x = 8 + 3x + -3x Combine like terms: 2x + -3x = -1x -6 + -1x = 8 + 3x + -3x Combine like terms: 3x + -3x = 0 -6 + -1x = 8 + 0 -6 + -1x = 8 Add '6' to each side of the equation. -6 + 6 + -1x = 8 + 6 Combine like terms: -6 + 6 = 0 0 + -1x = 8 + 6 -1x = 8 + 6 Combine like terms: 8 + 6 = 14 -1x = 14 Divide each side by '-1'. x = -14 Simplifying x = -14
| 11x+25=7x+1 | | 9x+7=4x-4 | | 5(y+3)=18-6y | | 5y-3x^3=127 | | 6x-1=15*-55 | | 4(4.5+2.5)-2y=5 | | 19x-6=6(x+3)-10 | | 2xy+4x-y=4 | | 4(9x+2)=153 | | P=-2b-3t-2t+b | | 46x-45x=1 | | 2w+30=60-x | | T=3a-4b+2a+b | | 3x-11=ax+6 | | x^2/3-11x/6-1=0 | | 10t-3=24 | | a/9=15 | | X-7x+6=30 | | 0=x+4-9x | | 2.6=-5.2(3.4+x) | | 0.1x=1.4 | | 34=-0.4(x+22) | | -0.26=logx | | -4(-5-b)= | | 3(x-9)=6(x+3) | | sinx=-0.95 | | 10x+15x-8+3=-2x+3-8 | | 7p-8=-3p+6 | | 2=4y-2y-6 | | 6e-15=15 | | x+37=3x+9 | | (x-8)+23-4=36 |